PKM Online Classroom Management Training Based on Google Classroom and Edpuzzle Applications at SMP Negeri 1 Probolinggo - Hefniy Hefniy; Yudik Al Farisi; Ach. Qusairi; Muhammad Amiruddin; Alip Al Mahdi; Muhammad Wahyu Fajry; Abdullah Haq Reshufle; Ahmad Nuvi; Muhammad Fadali Amar; M. Nurul Al Zaman; Moh. Hidayatullah; Siti Masruroh; Ahmad Muktashim Billah; Hoirul Anwar Maulana; Sodikin Sodikin; Moh. Hasyim (Universitas Nurul Jadid, 2021)
The purpose of this service activity is to improve the ability of teachers at SMP Negeri 1 Probolinggo in managing online classes by providing online class management training based on the Google Classroom and Edpuzzleapplications. The method of implementing this activity is lecture, practice, and discussions. Lectures were conducted to deliver material on the stages of classroom management using Google Classroom and using videos on Edpuzzle. The participants of this activity were all teachers of SMP Negeri 1 Probolinggo, a total of 40 people. For online class management, participants were given training in class management and grades, using forums, and making materials and quizzes. For the use of videos as learning materials, participants were trained in choosing videos, editing videos, inserting messages and questions, and multiple choices. The results of this service activity are as many as72.5% of participants have been able to manage online classes and integrate with Edpuzzle. Partners have also agreed to use Google Classroom's added puzzle for learning for the 2021/2022 academic year.